Aridity on the Canadian Plains - Sauchyn, David; Barrow, Elaine; Hopkinson, Ron; Leavitt, Peter (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThe Prairie Ecozone is the only major region of Canada where drought is a landscape hazard; aridity is linked to soil erosion. Management of prairie ecosystems and soil landscapes therefore requires an understanding of past and future trends and variability in regional aridity. We used instrumental and paleoclimatic records to define a regional baseline for prairie aridity, to evaluate the utility of modern climate normals (i.e. 1961-1990) as a benchmark for future climatic change, and to provide a historical context for a range of General Circulation Model (GCM) forecasts of regional aridity. A warm-dry scenario derived from the Canadian GCM projects a significant increase in the area of subhumid and semiarid climate. Tree rings and diatom-inferred lake salinity record prolonged arid events and show that the climate normal period of 1961-1990 may have been the most benign climate of the past 750 years. The climate of the 20th century was anomalous in terms of the absence of sustained drought. Because both lake and tree-ring analyses recorded an abrupt amelioration of climatic conditions near the start of the instrumental record, we suggest that the immediate impacts of future global warming may be to return the prairies to past conditions in which persistent aridity was recorded for intervals of decades or longer.